2008
DOI: 10.1074/jbc.m704768200
|View full text |Cite
|
Sign up to set email alerts
|

Makorin-2 Is a Neurogenesis Inhibitor Downstream of Phosphatidylinositol 3-Kinase/Akt (PI3K/Akt) Signal

Abstract: Makorin-2 belongs to the makorin RING zinc finger gene family, which encodes putative ribonucleoproteins. Here we cloned the Xenopus makorin-2 (mkrn2) and characterized its function in Xenopus neurogenesis. Forced overexpression of mkrn2 produced tadpoles with dorso-posterior deficiencies and small-head/shorttail phenotype, whereas knockdown of mkrn2 by morpholino antisense oligonucleotides induced double axis in tadpoles. In Xenopus animal cap explant assay, mkrn2 inhibited activin, and retinoic acid induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…During the reprogramming of mouse fibroblasts into induced pluripotent stem cells, Mkrn1 is co-regulated with a set of known differentiation markers (O'Malley et al, 2013). Also, ectopic Mkrn2 in Xenopus results in a smaller head and shorter tail than normal (Yang et al, 2008), a phenotype consistent with a precocious switch from proliferation to differentiation. These phenomena are consistent with a role for Mkrns in promoting differentiation by switching off LIN-28, which otherwise maintains an undifferentiated state.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…During the reprogramming of mouse fibroblasts into induced pluripotent stem cells, Mkrn1 is co-regulated with a set of known differentiation markers (O'Malley et al, 2013). Also, ectopic Mkrn2 in Xenopus results in a smaller head and shorter tail than normal (Yang et al, 2008), a phenotype consistent with a precocious switch from proliferation to differentiation. These phenomena are consistent with a role for Mkrns in promoting differentiation by switching off LIN-28, which otherwise maintains an undifferentiated state.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, Mkrn1 in mammals functions as an E3 ligase, targeting several proteins and even itself, although has not yet been identified as one of its targets (Kim et al, 2005;Salvatico et al, 2010;Lee et al, 2009Lee et al, , 2012Ko et al, 2012;Shimada et al, 2009;Ko et al, 2010;Kim et al, 2014;Cassar et al, 2015). In other contexts, Mkrns are also RNA-binding proteins, are localized to ribonucleoprotein granules, and have been found to sequester some mRNAs or promote their translation (Cano et al, 2010;Cassar et al, 2015;Gajdos et al, 2010;Kwon et al, 2013;Miroci et al, 2012;Cheung et al, 2010;Yang et al, 2008). Thus, an alternative mechanism for LEP-2/Mkrn function could be to sequester, protect from degradation and/or promote the translation of an mRNA encoding another protein that promotes LIN-28 destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of MKRN1 in murine embryonic nervous system and testis suggest that MKRN1 may have an important role in embryonic development and neurogenesis. Yang et al (2008) for the first time characterized the functional role of MKRN2 in Xenopus laevis and reported that MKRN2 plays a role in PI3 K/Akt-mediated neurogenesis during embryonic development of Xenopus. Expression studies of makorin genes (MKRN1 and MKRN2) in yellowtail fish (Chamnan et al 2003), mouse and humans (Gray et al 2000(Gray et al , 2001 and Xenopus (Yang et al 2008) have paved a way for an understanding of this gene family in animal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2008) for the first time characterized the functional role of MKRN2 in Xenopus laevis and reported that MKRN2 plays a role in PI3 K/Akt-mediated neurogenesis during embryonic development of Xenopus. Expression studies of makorin genes (MKRN1 and MKRN2) in yellowtail fish (Chamnan et al 2003), mouse and humans (Gray et al 2000(Gray et al , 2001 and Xenopus (Yang et al 2008) have paved a way for an understanding of this gene family in animal systems. MKRN has been shown to act as an E3 ligase for hTERT (Kim et al 2005), as a transcriptional co-regulator of androgen and retinoic acid receptors (Omwancha et al 2006), and also for both p53 and p21 (Lee et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation